The Relationship of Breakfast’s Nutrient Intake and Nutritional Status with Physical Fitness of 4th Grade Students In Urban Area SDN Cililitan 02 Jakarta Timur - Siti Zahrah; Titus Priyo Harjatmo; Tugiman A; Endang Titi A; Alfiantani Nugroho (Politeknik Kesehatan Kemenkes Jakarta II, 2022)
Physical Fitness is very needed for primary school-age children’s development because the growth and development in this period of age are very fast, both physically and spiritually. Before starting activities at school, children need an adequate intake from their breakfast. This research aims to know the relationship between breakfast’s nutrition intake and nutritional status with physical fitness of 4th grade students in urban area SDN Cililitan 02 Jakarta Timur. This type of research is Analytical study with cross sectional design with total sample 77 people and were taken by systematic random sampling which qualified the inclusion in this research’s needed. Physical fitness data was obtained based on the Triple Hop Test. Breakfast’s nutrition intake from food recall 1x24 hours method in the school’s time. Nutritional Status Data (BMI) is measured using the anthropometric method. Data analysis with Frequency Distribution and Chi-Square Test. From 77 respondents, almost of them have a good physical fitness at 63.6 %, Good Nutritional Status Data (BMI) at 49.4 %, Adequate energy intake 80.5 %, Adequate protein intake 53.2 %, Adequate fat intake 83.1 % and Adequate carbohydrate intake 89.6 %. There is no relationship between nutritional status and physical fitness (p=0.213) and similarly there is no relationship between protein intake and physical fitness (p=0.669). There is a significant relationship between energy intake, fat intake, and carbohydrate intake with physical fitness (p=0.047), (p=0.024), and (p=0.011).